Situation Report: Bulgaria, 5 August 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Bulgaria and Recent Events in the Sudan Todor Zhivkov at Buzludzha and in the Crimea Military Maneuvers to Be Held in Bulgaria Alcoholism among Youth